Knowledge, prevalence and seroconversion for hepatitis B in health professionals acting in a private clinic - Adriana D. BETTA; Claudinei M. SILVA; Jorge V. TEIXEIRA; Leyde D. PEDER (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: The aim of the present study was to evaluate the knowledge, prevalence and seroconversion to hepatitis B in health professionals. Methods: A descriptive and quantitative research was conducted through the application of questionnaires, examination analysis and immunization records of employees of a private health clinic in Cascavel, Paraná. Results: Of the 96 employees, 87 (90.6%) had anti-HBs reagent verified by the exam. Of these, the majority of employees were female (91.6%), had knowledge of the hepatitis B virus (HBV) (96.3%) and were between 31 and 40 years old (47.4%). Also, they had not had an accident with biological material (86.5%), had no HBV carrier (87.4%), or had had contact with carriers of the infection (90.6%). Conclusion: Although the most effective prevention method against HBV is vaccination, approximately 10% of the employees did not have antibodies detected by the test. In addition, some individuals showed little knowledge about hepatitis B, which is of concern, as they are health professionals who are at risk of acquiring infections due to contact with patients and biological materials.